Leadership in Action : Issues and Observations - How Changing Realities and Perceptions Affect You as a Leader - King, Robert J. Lee. Sara N. (Center for Creative Leadership, 2001)
Many organizations have become so diffuse and pluralistic that old, static models no longer hold.